Analisis Manfaat Wakaf Produktif dalam QS. Al-Baqarah [2]: 261 melalui Pendekatan Sosiolinguistik - Syaiful Efendi; Arsal; Helfi (AL QUDS : Jurnal Studi Alquran dan Hadis, 2025)
This article analyzes agrarian metaphors and the construction of the meaning of philanthropy of productive waqf in QS. Al-Baqarah [2]: 261 with a sociolinguistic approach based on the function of language and social context. This research departs from the view that the metaphor and language style of the Qur’an not only function as rhetorical ornaments, but also as communication strategies that reflect the socio-economic reality of the first speaking community. Using qualitative-descriptive methods and a text-analysis design, this study examines agrarian diction, the structure of similitudes (tasybīh), and the communicative function of verse in relation to the social context of Arab society, particularly the agrarian community of Medina at the time of revelation. The main data is in the form of QS. Al-Baqarah [2]: 261 is analyzed together with classical and contemporary interpretations, sociolinguistic literature, and studies on productive waqf. The results of the study show that agrarian metaphors such as ḥabbah (seed), sanābil (stalk), and yuḍā'if (multiplication) underpin philanthropic meanings that emphasize productivity, sustainability, and the expansion of property benefits. The metaphor functions informatively, persuasively, and legitimately in framing waqf as socio-economic capital that continues to grow, rather than merely as a consumptive donation. These findings confirm that QS. Al-Baqarah [2]: 261 provides the linguistic, social, and theological basis for the concept of productive waqf. Theoretically, this study enriches the study of Islamic philanthropy by demonstrating the relevance of sociolinguistic approaches in revealing the relationship between the Qur’an’s linguistic structure and the construction of the ummah’s socio-economic values.